Penerapan Metode Muroja’ah dalam Menghafal Al-Qur’an di Madrasah Ibtidaiyah Ma’arif Soka Poncowarno Kebumen - Sukriyah, Umdatus; Khasanah, Nginayatul (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
The muroja’ah method is a way of memorizing the Qur’an by repeating memorization. By applying the muroja’ah method can help in maintaining the memorization of the Qur’an. This study aims to determine the use of the muroja’ah method in memorizing juz ‘amma or Al-Qur’an juz 30, as well as knowing the supporting and inhibiting factors in memorization using the muroja’ah method. The research locations is MI Ma’arif Soka Poncowarno Kebumen. The theory used is the teory of memorizing the Qur’an by repetition. Data collections techniques in the form of observation, interviews and document studies. The results of the study are the application of the muroja’ah method in memorizing the Qur’an juz 30 in students in MI Ma’arif Soka Poncowarno Kebumen is a joint memorization guided by ustadz ustadzah companion and memorizing individually to listen ustadz ustadzah companion. Supporting factors and the application of the muroja’ah method, namely there are subjects that support the learning of tahfidz juz ‘amma, motivational support from the madrasah, supports from parents of students and the desire of students to achieve their memorizations targets. Then there are inhibiting factors in the application of the muroja’ah method, namely the existence of students who have not been able to read hijaiyah letters, some parents or gusrdians of students who do not support their children in learning, the emergence of baredom and laziness in students in memorizing juz ‘amma, and the shyness of students to ustadz ustadzah companion when they have not memorized